Arteriovenous Malformations Treated With Frameless Robotic Radiosurgery Using Non-Invasive Angiography: Long-Term Outcomes of a Single Center Pilot Study - Kelly, Ryan; Conte, Anthony; Nair, M. Nathan; Voyadzis, Jean-Marc; Anaizi, Amjad; Collins, Sean; Kalhorn, Christopher; Stemer, Andrew; Mai, Jeffery; Armonda, Rocco; Lischalk, Jonathan; Berkowitz, Frank; et al. (Frontiers in Oncology, 2020)
Objective: CT-guided, frameless robotic radiosurgery is a novel radiotherapy technique for the treatment of intracranial arteriovenous malformations (AVMs) that serves as an alternative to traditional catheter-angiography targeted, frame-based methods. Methods: Patients diagnosed with AVMs who completed single fraction frameless robotic radiosurgery at Medstar Georgetown University Hospital between July 20, 2006 – March 11, 2013 were included in the present study. All patients received pre-treatment planning with CT angiogram (CTA) and MRI, and were treated using the CyberKnife radiosurgery platform. Patients were followed for at least four years or until radiographic obliteration of the AVM was observed. Results: Twenty patients were included in the present study. The majority of patients were diagnosed with Spetzler Martin Grade II (35%) or III (35%) AVMs. The AVM median nidus diameter and nidal volume was 1.8 cm and 4.38 cc respectively. Median stereotactic radiosurgery dose was 1800 cGy. After a median follow-up of 42 months, the majority of patients (81.3%) had complete obliteration of their AVM. All patients who were treated to a total dose of 1800 cGy demonstrated complete obliteration. One patient treated at a dose of 2200 cGy developed temporary treatment-related toxicity, and one patient developed post-treatment hemorrhage. Conclusions: Frameless robotic radiosurgery with non-invasive CTA and MRI radiography appears to be a safe and effective radiation modality and serves as a novel alternative to traditional invasive catheter-angiography, frame-based methods for the treatment of intracranial AVMs. Adequate obliteration can be achieved utilizing 1800 cGy in a single fraction, and minimizes treatment-related side effects.